Targeted imaging of integrins in cancer tissues using photocleavable Ru(ii) polypyridine complexes as mass-tags. Issue 44 (29th April 2020) - Han, Jiaying; Sun, Jing; Song, Shanshan; Beljaars, Leonie; Groothuis, Geny M. M.; Permentier, Hjalmar; Bischoff, Rainer; Halmos, Gyorgy B.; Verhoeven, Cornelia J.; Amstalden van Hove, Erika R.; Horvatovich, Peter; Casini, Angela
Abstract : A novel photocleavable ruthenium-based mass-tag for mass spectrometry imaging of proteins in cancer tissues. Abstract : Targeted epitope-based mass spectrometry imaging (MSI) utilizes laser cleavable mass-tags bound to targeting moieties for detecting proteins in tissue sections. Our work constitutes the first proof-of-concept of a novel laser desorption ionization (LDI)-MSI strategy using photocleavable Ru(ii ) polypyridine complexes as mass-tags for imaging of integrins αvβ3 in human cancer tissues.